2017
DOI: 10.1371/journal.pone.0185000
|View full text |Cite
|
Sign up to set email alerts
|

Female reproductive success and calf survival in a North Sea coastal bottlenose dolphin (Tursiops truncatus) population

Abstract: Between-female variation in reproductive output provides a strong measure of individual fitness and a quantifiable measure of the health of a population which may be highly informative to management. In the present study, we examined reproductive traits in female bottlenose dolphins from the east coast of Scotland using longitudinal sightings data collected over twenty years. From a total of 102 females identified between 1997 and 2016, 74 mothers produced a collective total of 193 calves. Females gave birth f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
14
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 49 publications
6
14
2
1
Order By: Relevance
“…The age of first pregnancy was recorded to be 7.5 yr, which is within the ranges reported for other bottlenose dolphin populations (Fruet et al 2015, Robinson et al 2017, Kemper et al 2019. In captivity, a bottlenose dolphin female typically begins to be reproductive at 7−10 yr, but may also begin earlier, between 5 and 7 yr (Schroeder 1990).…”
Section: First Reproductionsupporting
confidence: 75%
See 3 more Smart Citations
“…The age of first pregnancy was recorded to be 7.5 yr, which is within the ranges reported for other bottlenose dolphin populations (Fruet et al 2015, Robinson et al 2017, Kemper et al 2019. In captivity, a bottlenose dolphin female typically begins to be reproductive at 7−10 yr, but may also begin earlier, between 5 and 7 yr (Schroeder 1990).…”
Section: First Reproductionsupporting
confidence: 75%
“…Groups of bottlenose dolphins with calves were previously found to be significantly larger than those without calves (Hubard et al 2004, Blasi & Boitani 2012, and in this study the number of calves produced was influenced by the mean maternal group size. The trend of finding calves in larger groups suggests that larger group size may benefit mother−calf pairs (Schaffar-Delaney 2004, Gibson & Mann 2008, Robinson et al 2017; however, in this study, the number of calves per female was not significantly related to the strength of the associations of the mother. In Sarasota Bay, Florida (USA), Wells (1991a) showed that survivorship of bottlenose dolphin calves was related to group size.…”
Section: Female Productivity Group Size and Association Patternscontrasting
confidence: 62%
See 2 more Smart Citations
“…Many dolphin species or populations are recognized internationally as vulnerable or threatened due to their low reproductive potential, which is, giving birth to one calf after a long gestation period of 11-12 months [15,16]. Oil spills and various fishing methods, most notably purse-seine fishing for tuna and the use of drift and other gill nets, results in large amounts of dolphins being killed accidentally [17].…”
Section: Open Access Freely Available Onlinementioning
confidence: 99%